Pandemic Media Preliminary Notes toward an Inventory - Keidl, Philipp Dominik; Melamed, Laliv; Hediger, Vinzenz; Somaini, Antonio (Configurations of Film, 2020)
With its unprecedented scale and consequences the COVID-19 pandemic has generated a variety of new configurations of media. Responding to demands for information, synchronization, regulation, and containment, these "pandemic media" reorder social interactions, spaces, and temporalities, thus contributing to a reconfiguration of media technologies and the cultures and polities with which they are entangled. Highlighting media's adaptability, malleability, and scalability under the conditions of a pandemic, the contributions to this volume track and analyze how media emerge, operate, and change in response to the global crisis and provide elements towards an understanding of the post-pandemic world to come.